Pica is associated with lower willingness to change negative habits of diet and exercise, inadequate lifestyle, and less healthful food consumption in dialysis - Orozco-González, Claudia N.; Marquez-Herrera, Roxana M.; Martín-del-Campo, Fabiola; Cortés-Sanabria, Laura; Villasana-Ballesteros, Mariana; Cueto-Manzano, Alfonso M. (Frontiers in Nutrition, 2024)
In dialysis patients, on the one hand unwillingness to change negative lifestyle patterns is associated with worse nutritional status and unhealthy lifestyle, whereas on the other, pica may be highly prevalent. However, it is not known whether pica is associated with unwillingness to change negative lifestyle behaviors, as well as with consumption of different types of foods. This study aimed to investigate this issue.Methods: This is a cross-sectional study in dialysis patients. Lifestyle was assessed using the self-administered Instrument to Measure Lifestyle Questionnaire (IMEVID). Pica diagnosis was established according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. A food frequency questionnaire was performed and self-reported willingness to change was determined by a trans-theoretical model staging inventory.Results: Compared with patients without pica, those with pica (particularly hard pica) had lower willingness to change unhealthy behavior in the case of diet (22% vs 46% in precontemplation/contemplation stages, respectively) and exercise (43% vs 62% in precontemplation/contemplation stages, respectively). Patients with hard pica had significantly (p<0.05) lower scores in almost all dimensions of the lifestyle questionnaire than those in the no pica group: diet (23.9 vs 26.8, respectively), physical activity (5.5 vs 7, respectively), knowledge of disease (5.7 vs 6.4, respectively), emotion management (6.6 vs 8, respectively) and adherence to treatment (13.4 vs 14.7, respectively), but not in the consumption of tobacco and alcohol. Compared to patients with no pica, those with hard pica ate vegetables and fruits less frequently, and dairy products, fried foods and soda more frequently.Conclusions: Pica was more frequently observed in patients with lower willingness to change negative habits of diet and exercise, in those who had more unhealthy behaviors in diet, exercise and emotion management dimensions and adherence to treatment, as well as in those who ate less frequently healthful foods and more frequently unhealthy foods.